AL-FĀTIḤAH AS A PARADIGM OF INTERPRETATION - Wardani Wardani (Institut Agama Islam Negeri (IAIN) Ponorogo, 2021)
Thought on the methodology of interpreting the Qur'an in Indonesia cannot be separated from several contemporary Muslim scholars. Some of them gave a new explanation that developed from the treasures of classical concepts. This paper discusses the thoughts of M. Dawam Rahardjo, one of the contemporary Muslim scholars, on al-Fātiḥah as a paradigm of interpretation of the Qur'an. This surah, based on the explanation of the Prophet Muhammad, is only referred to as